2010
DOI: 10.1007/s10610-010-9128-5
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Modelling Approach to Predict Adolescent Offending Behaviour from Family, School and Community Factors

Abstract: It seems undeniable that immediate social contexts exert an important influential role on adolescent behavioural adjustment. Research thus far has found that certain family, school and community/neighbourhood environment characteristics may influence a youth's involvement in risk activities such as antisocial behaviour and drug use, and even delinquent behaviour. However, the mechanisms that link these characteristics to such behaviours have not yet been thoroughly analysed and prior research has focused mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…These findings coincided with the vast amount of research that reports that positive, open, and fluid communication is related to a lower involvement in aggressive behavior in the child, both in traditional bullying (Galvin et al 2015;Ledwell and King 2015) as in cyberbullying (Appel et al 2014;Buelga et al 2017). On the contrary, communication that is not very fluid or negative with parents is associated with a greater participation by children in antisocial and violent behavior (Braithwaite et al 2017;Carrascosa et al 2016;Estévez and Emler 2010). In this regard, in a study conducted by Buelga et al (2015), it was observed that cyberbullies presented inadequate patterns of family communication, characterized by offensive communication, full of negative and unclear messages.…”
Section: Discussionmentioning
confidence: 99%
“…These findings coincided with the vast amount of research that reports that positive, open, and fluid communication is related to a lower involvement in aggressive behavior in the child, both in traditional bullying (Galvin et al 2015;Ledwell and King 2015) as in cyberbullying (Appel et al 2014;Buelga et al 2017). On the contrary, communication that is not very fluid or negative with parents is associated with a greater participation by children in antisocial and violent behavior (Braithwaite et al 2017;Carrascosa et al 2016;Estévez and Emler 2010). In this regard, in a study conducted by Buelga et al (2015), it was observed that cyberbullies presented inadequate patterns of family communication, characterized by offensive communication, full of negative and unclear messages.…”
Section: Discussionmentioning
confidence: 99%
“…Normative obligation to obey the law was measured with a single item, "I feel like it is sometimes okay to break the law", on a 7-point Likert scale ranging from (1) "strongly agree" to (7) "strongly disagree." This item was created for the current study based on existent work (e.g., Estévez and Emler 2010, Fine et al 2020, Reisig, Bratton, and Gertz 2007. Higher scores indicated greater normative obligation to obey the law.…”
Section: Descriptive Social Norms Participants Rated To What Extent mentioning
confidence: 99%
“…These studies however focus on a singular system or two developmental distal-proximal systems like neighborhood (distal) and parenting (proximal). Estévez and Emler ( 2010 ) did study multiple contexts like family, community, and attitude toward school but peer relationships were not included in their study. In their attempt to understand adolescents, Neumann and colleagues reported effects of risk in neighborhood and adolescent characteristics relationship to be mediated by risk in the parenting domain (Newmann, Barker, Koot, & Maughan, 2010 ).…”
Section: Multiple Context Approachmentioning
confidence: 99%